AN ANALYSIS OF STUDENTS' ABILITY IN WRITING NARRATIVE TEXTS : A Case study at One Public Junior High Schools in Bandung - Mulyaningsih, Dini Utami (2013)
Penelitian ini fokus pada analisis tulisan siswa dalam menulis teks naratif yang bertujuan untuk mengetahui kemampuan siswa dalam hal schematic structure dan linguistic featuresdari teks naratif. Penelitian in dilaksanakan dikelas delapan sebuah sekolah menengah pertama di Bandung. Studi Kualitatif digunakan dalam penelitian ini. Data penelitian didapatkan dari hasil tulisan siswa yang kemudian dianalisis berdasarkan schematic structuredan linguistic featuresdari sebuah teks naratif. Hasil dari analisis teks siswa menunjukan bahwa siwa yang tergolong dalam katagori low dan middle achiever tidak mempunyai kemampuan yang cukup baik dalam menulis teks naratif. Siswa dalam katagori ini masih membutuhkan banyak bimbingan dari guru. Sedangkan untuk katagori high achiever, guru hanya perlu mengingatkan siswa untuk membaca kembali hasil tulisan siswa tersebut untuk mencegah kesalahan kecil. Oleh sebab itu, penggunaan teknik dan pendekatan dalam mengajar yang cocok harus diterapkan. ABSTRACT This study focused onthe analysis of students' ability in writing narrative texts. It was aimed to examinestudents' ability in writing narrative texts in terms of schematic structure and linguistic features. This research was conducted in a class of eight grade students in one public junior high school in Bandung. Aqualitative case was used in this study. The data were collected through students' writing. The data from the instrumentwere analyzed qualitatively in terms of the schematic structure and linguistic features. The analysis of the data indicated that students from low and middle achievers have insufficient knowledge of writing narrative. It can be seen from schematic structure and the number of linguistic features of the text. Moreover, the students from low and middle achiever still need a lot of writing guidance from the teacher. Furthermore, for high achiever, the teacher only needs to remind the student to readagain the text for several times to avoid minor mistakes. Hence, appropriate teaching techniques and approaches should be implemented.